Fishermen's Perception of Direct Cash Assistance during The Covid-19 Pandemic (Kalumpangloe Village Case of Arungkeke Subdistrict Jeneponto) - Bahtiar, Syuhardiman; Arief, Andi Adri; Cangara, Arie Syahruni (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2024)
This study aims to determine Fishermen's perceptions of cash transfers in Kalumpangloe Village, Arungkeke District, Jeneponto Regency during the pandemic. This research was conducted from February to March 2021 in Kalumpangloe Village, Arungkeke District, Jeneponto Regency, South Sulawesi. The method that we used is Non-Probability Sampling. The data source that we used are primary data and secondary data. The data analysis method used in this research is quantitative and qualitative. Meanwhile, for quantitative data analysis, the Likerts scale was used to determine the fishermen's perception of cash transfer. Cash transfers implementation mechanism starts from the stage of socialization, data verification, information, disbursement and evaluation. Perceptions of fishermen in Kalumpang Loe Village, Jeneponto Regency, obtained through 4 indicators, it's known that the village community considers that cash transfers is very useful as assistance to provides their necessities, but they didn't use to provides business fund. The process of sending cash transfers was not filled the promised time and the target, and also the target of cash transfers recipients that is set by the government already reaches it's target. The allocation of cash transfers by the people of Kalumpangloe Village is as much as 55% for food needs, 8% for clothing needs, 4% for housing needs, 14% used as bussines fund, 17% used for children's education costs, and 2% for other allocations. Where the amount of cash transfers funds is IDR 300,000/month.